Differential Impact of Cysteine Cathepsins on Genetic Mouse Models of De novo Carcinogenesis: Cathepsin B as Emerging Therapeutic Target - Reinheckel, Thomas; Peters, Christoph; Krüger, Achim; Turk, Boris; Vasiljeva, Olga (Frontiers in Pharmacology, 2012)
Lysosomal cysteine cathepsins belong to a family of 11 human proteolytic enzymes. Some of them correlate with progression in a variety of cancers and therefore are considered as potential therapeutic targets. Until recently, the contribution of individual cathepsins to tumorigenesis and tumor progression remained unknown. By crossing various types of mouse cancer models with mice where specific cathepsins have been ablated, we contributed to this gap of knowledge and will summarize the results in this report. The employed models are the Rip1-Tag2 model for pancreatic neuroendocrine tumors, the K14-HPV16 model for squamous skin and cervical cancers, and the MMTV-PyMT model for metastasizing breast cancer, the KPC model for pancreatic ductal adenocarcinoma, and the APCmin mice developing early stages of intestinal neoplasia. All models harbor mutations in relevant tumor suppressors and/or cell-type specific expression of potent oncogenes, which initiate de novo carcinogenesis in the targeted tissues. In all these models deletion of cathepsin B led to suppression of the aggressiveness of the respective cancer phenotype. Cathepsin B may network with other proteases as it was shown for cathepsin X/Z. In contrast, deletion of cathepsin L was beneficial in the RiP1-Tag2 model, but enhanced tumorigenesis in the APCmin, and the K14-HPV16 mice. A logical consequence of these results would be to further pursue selective inhibition of cathepsin B. Moreover, it became clear that cathepsins B and S derived from cells of the tumor microenvironment support cancer growth. Strikingly, delivery of broad spectrum cysteine cathepsin inhibitors in the tumor microenvironment disrupts the permissive ecosystem of the cancer and results in impaired growth or even in regression of the tumor. In addition, combination of cysteine cathepsin inhibition and standard chemotherapy improves the therapeutic response of the latter.